2018
DOI: 10.15296/ijwhr.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Markers in Early Pregnancy Loss: A Case-Control Study

Abstract: Objectives: Evidence suggests that oxidative stress (OS) plays a prominent role in the pathophysiology of pregnancy complications in women. The present study was conducted to determine the levels of OS markers in early pregnancy loss and to compare the results with those in healthy pregnant women. Materials and Methods: A total of 32 women with early pregnancy loss and 32 healthy women in the first trimester of pregnancy, with similar demographic characteristics entered this study as the cases and controls. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Parallely, involvement of OS in RPL cases in relation to control was evidenced by Safronova et al (2003) . Concamitant with ROS, altered and impaired antioxidant status (TAC) was reported by Torkzahrani et al,2019 with impaired antioxidant defense correlating with spontaneous abortions ( Torkzahrani et al, 2019 ). Parallely, in an Egyptian study, a weekened antioxidant defense with surplus free radicals was reported demonstrating role of oxidative damage in RPL ( El-Far et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Parallely, involvement of OS in RPL cases in relation to control was evidenced by Safronova et al (2003) . Concamitant with ROS, altered and impaired antioxidant status (TAC) was reported by Torkzahrani et al,2019 with impaired antioxidant defense correlating with spontaneous abortions ( Torkzahrani et al, 2019 ). Parallely, in an Egyptian study, a weekened antioxidant defense with surplus free radicals was reported demonstrating role of oxidative damage in RPL ( El-Far et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a state of imbalance between the production of ROS (reactive oxygen species) and the ability of the body’s natural defense mechanisms (antioxidants) to contend with and protect against the effects of these reactive compounds. Disruption in these processes results in uncontrollable changes, which leads to a series of complications in the functioning of the body, permanent cellular damage, and subsequent degeneration [ 138 , 139 ]. Currently, there are no relevant reports on the involvement of the FOXO signaling pathway in miscarriage.…”
Section: Resultsmentioning
confidence: 99%